Philosophy and Philology: Two Approaches of Commentating the Shen Nong Ben Cao Jing (Shen Nong's Classic of the Materia Medica) in the Ming and Qing Dynasties - Che-chia CHANG (Wolters Kluwer Health/LWW, 2023)
This paper tests the hypothesis that the commentary trend of the Shen Nong Ben Cao Jing (Shen Nong's Classic of the Materia Medica) arises alongside the fashionable philology of the time, or the aversion against the Jin-Yuan medical philosophy. After surveying 12 major commentaries, it is concluded that the situation is more complicated than a simple assertion. The seemingly opposite philosophy and philology approaches have been used eclectically to innovate the understanding of ancient traditional Chinese medicine texts.